Effectiveness Of Automated Enforcement System (Aes) In Reducing Red Light Violation (Rlv) Behaviours: A Case Study In Kuala Lumpur - Kabit, M.R.; Sabihin, N.A.; Wan Ibrahim, W.H. (JCECT, 2016)
The national statistics indicates that red light violations (RLV) have become a significant safety problem throughout the nation. As a result, the Malaysian government has initiated the installation of automated enforcement system (AES) to reduce RLV related crashes at identified critical locations particularly in Kuala Lumpur region. The primary aim of this study was to evaluate the effectiveness of AES installation in reducing RLR at signalised intersections using a case study at Jalan Ipoh, Kuala Lumpur. Before and after AES installation data were collected and were analysed using a statistical tool. T-test results indicated that the installation of AES has significantly reduced RLV behaviours at the studied signalised intersection. The results of this study provide a useful insight on the benefits of AES in decreasing intersection related crashes by means of reducing RLV behaviours among the road users through AES installation.